2007
DOI: 10.1002/jsfa.3080
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of fatty acids in edible organs and seed fractions of borage (Borago officinalis L.)

Abstract: BACKGROUND: Borage (Borago officinalis L.) is currently used as a vegetable in the north of Spain. The edible parts of the plant are the petioles, leaves and stems. The objective of this study was to determine the oil and fatty acids content in the edible tissues (leaves, petioles and stems) and seed fractions (endosperm + cotyledon, seed coat and elaiosome) of white-and blue-flowered borage accessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 15 publications
7
39
2
Order By: Relevance
“…A content of lipids established in fresh borage leaves in this study is in line with that determined on a dry mass basis by del Río-Celestino et al [2008]. The composition of the leaf lipids with palmitic, α-linolenic and linoleic + linolelaidic acids as the major components and with approximate content of myristic and lauric acids was similar to those stated by Griffiths et al [1996], Sayanova et al [1999] and del Río-Celestino et al [2008].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A content of lipids established in fresh borage leaves in this study is in line with that determined on a dry mass basis by del Río-Celestino et al [2008]. The composition of the leaf lipids with palmitic, α-linolenic and linoleic + linolelaidic acids as the major components and with approximate content of myristic and lauric acids was similar to those stated by Griffiths et al [1996], Sayanova et al [1999] and del Río-Celestino et al [2008].…”
Section: Discussionsupporting
confidence: 90%
“…Griffiths et al [1996] and del Río-Celestino et al [2008] reported a substantial content of stearidonic acid but this component was not determined in this experiment. Griffiths et al [1996], Sayanova et al [1999] and del Río-Celestino et al [2008] also found a few percentage content of γ-linolenic acid, however this component was not detected in this study. Alike, erucic acid established in very low quantities in the borage leaf lipids by del Río-Celestino et al [2008] was not detected in the present research.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations